Peran Self Monitoring sebagai Mediator antara Job Characteristics dan Well-Being pada Guru Sekolah Inklusi - Ulifa Rahma; Zahratul Fauza; Faizah Faizah; Yuliezar Perwira Dara (Universitas Negeri Surabaya, 2021)
This study aims to determine the role of teacher self-monitoring as a mediator between job characteristics (emotional job demands and trust in colleagues) and teacher well-being teachers in inclusive schools. The sample of this study was 204 teachers in Indonesia from elementary to high school levels in inclusive schools using G*power. The sample selection technique in this study was accidental sampling teachers in Indonesia from elementary to high school levels in inclusive schools. The research method used is correlational quantitative research. This study uses four measuring instruments, namely the teacher well being scale, the self-monitoring scale, and, to measure job characteristics, the omnibus trust and the emotional job demand scales. Analysis of research data refers to Baron & Kenny using process modeling analysis version 3.0 by Andrew Hayes. As a result, self monitoring is able to become a mediator between emotional job demand and teacher well-being. Self monitoring has also proven to be a mediator between trust in colleagues and teacher well-being.Keywords: Job characterstics, self monitoring, well-being, teacher, inclusive schoolAbstrak: Penelitian ini bertujuan mengetahui peran teacher self monitoring sebagai mediator antara job characteristic (emotional job demands dan trust in colleagues) dan teacher well-being guru disekolah inklusi. Sampel dalam penelitian 204 guru dari jenjang Pendidikan Sekolah Dasar sampai dengan Sekolah Menengah Atas di sekolah inklusi menggunakan aplikasi G*power. Teknik pemilihan sampel dalam penelitian ini adalah accidental sampling yaitu seluruh guru inkusi yang ditemui dari jenjang Sekolah Dasar sampai Menengah Atas. Metode penelitian yang digunakan adalah penelitian kuantitatif korelasional. Penelitian ini menggunakan empat alat ukur, yaitu skala teacher well being, self monitoring dan, untuk mengukur job characteristics, skala omnibus trust dan emotional job demand. Analisis data penelitian mengacu pada Baron & Kenny menggunakan analisis process modeling versi 3.0 oleh Andrew Hayes. Hasilnya self monitoring mampu menjadi mediator antara emotional job demand dan teacher well-being. Self monitoring juga terbukti mampu menjadi mediator antara trust in colleagues dan teacher well-being.